2012
DOI: 10.1051/0004-6361/201118710
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic field of IRAS 16293-2422 as traced by shock-induced H2O masers

Abstract: Context. Shock-induced H 2 O masers are important magnetic field tracers of very high density gas. Water masers are found in both high-and low-mass star-forming regions, and are a powerful tool for comparing magnetic field morphologies in both mass regimes. Aims. We present one of the first magnetic field determinations for the low-mass protostellar core IRAS 16293-2422 at volume densities as high as 10 8−10 cm −3 . Our goal is to determine wether the collapsing regime of this source is controlled by magnetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…If B = 10 µG in the initial (pre-collapse) volume of radius 0.1 pc and assuming field freezing, the magnetic field strength in the final (postcollapse) volume of radius 100 AU is about 400 mG. This naive estimate is comparable within a factor of 2 with the value found by Alves et al (2012) who estimate B ≈ 200 mG from observations of shock-induced H 2 O masers. This is an averaged quantity, but Imai et al (2007) computed the position of the H 2 O masers, and found the farther one to be at about 110 AU.…”
Section: Accretion Flows In Collapsing Envelopessupporting
confidence: 64%
“…If B = 10 µG in the initial (pre-collapse) volume of radius 0.1 pc and assuming field freezing, the magnetic field strength in the final (postcollapse) volume of radius 100 AU is about 400 mG. This naive estimate is comparable within a factor of 2 with the value found by Alves et al (2012) who estimate B ≈ 200 mG from observations of shock-induced H 2 O masers. This is an averaged quantity, but Imai et al (2007) computed the position of the H 2 O masers, and found the farther one to be at about 110 AU.…”
Section: Accretion Flows In Collapsing Envelopessupporting
confidence: 64%
“…The Gaussian fit to these data peaks closer to v LSR = 3.2 km s −1 , indicative indeed of resolved velocity structure. Outflow emission (cf., Loinard et al 2012 scales (Alves et al 2012), could explain this velocity shift, but it is not possible to deduce its importance from the current data.…”
Section: Resultsmentioning
confidence: 75%
“…Alves et al 2012;Amiri et al 2012;Leal-Ferreira et al 2012;Vlemmings et al 2011Vlemmings et al , 2006b). Both single-dish and interferometric observations have revealed that silicon monoxide (SiO), water (H 2 O), hydrogen cyanide (HCN), hydroxyl (OH), and methanol (CH 3 OH), among others, can naturally generate polarized maser emission in these enviroments (e.g.…”
Section: Introductionmentioning
confidence: 99%